Time Is Not More Abstract Than Space in Sound - Kranjec, Alexander; Lehet, Matthew; Woods, Adam J.; Chatterjee, Anjan (Frontiers in Psychology, 2019)
Time is talked about in terms of space more frequently than the other way around. Some have suggested that this asymmetry runs deeper than language. The idea that we think about abstract domains (like time) in terms of relatively more concrete domains (like space) but not vice versa can be traced to Conceptual Metaphor Theory. This theoretical account has some empirical support. Previous experiments suggest an embodied basis for space-time asymmetries that runs deeper than language. However, these studies frequently involve verbal and/or visual stimuli. Because vision makes a privileged contribution to spatial processing it is unclear whether these results speak to a general asymmetry between time and space based on each domain’s general level of relative abstractness, or reflect modality-specific effects. The present study was motivated by this uncertainty and what appears to be audition’s privileged contribution to temporal processing. In Experiment 1, using an auditory perceptual task, temporal duration and spatial displacement were shown to be mutually contagious. Irrelevant temporal information influenced spatial judgments and vice versa with a larger effect of time on space. Experiment 2 examined the mutual effects of space, time, and pitch. Pitch was investigated because it is a fundamental characteristic of sound perception. It was reasoned that if space is indeed less relevant to audition than time, then spatial distance judgments should be more easily contaminated by variations in auditory frequency, while variations in distance should be less effective in contaminating pitch perception. While time and pitch were shown to be mutually contagious in Experiment 2, irrelevant variation in auditory frequency affected estimates of spatial distance while variations in spatial distance did not affect pitch judgments. Results overall suggest that the perceptual asymmetry between spatial and temporal domains does not necessarily generalize across modalities, and that time is not generally more abstract than space.